Một số biện pháp phát triển năng lực giải quyết vấn đề toán học cho học sinh trong dạy học chủ đề “Hình học trực quan” (Toán 8) - Phan , Văn Lý; Lê , Thị Thanh (Tạp chí Giáo dục, 2023)
The current educational innovation trend in our country is to strongly shift the educational process from mainly equipping knowledge to comprehensively developing learners’ competence and qualities. In particular, the competence to solve mathematical problems is one of the basic competencies that need to be formed and developed for students. The study presents three measures to develop students’ competence to solve mathematical problems in teaching the topic “Visual geometry” (Math 8). Teaching practice shows that the proposed measures are appropriate and feasible, initially contributing to improving teaching quality and meeting the educational innovation goals specified in the 2018 General Education Program in Maths.